Surgical training in the Caribbean: The past, the present, and the future - Newnham, Mark S.; Dan, Dilip; Maharaj, Ravi; Plummer, Joseph Martin (Frontiers in Surgery, 2023)
The six million inhabitants of these diverse English-speaking Caribbean countries are grateful to the University of the West Indies, which has been central in the independent training of surgical specialists in all areas of surgery for the past 50 years. Similar to the per capita income, the quality of surgical care, albeit acceptable, is quite variable throughout the region. Globalization and access to information have revealed that the quality of training and surgical care being delivered can be further improved. Technological advances will perhaps never be on par with higher-income countries, but collaborative ventures with global health partners and institutions can ensure that the people of the region will have appropriately trained surgical doctors and, therefore, the provision of accessible quality care will remain a staple, with even the possibility of income generation. This study reviews the journey of our structured surgical training program delivered in the region and outlines our growth plans.